Principals’ Instructional Supervision Practices: Key to Kiswahili Academic Performance - Rose Mwanza; Lucia Musyoka (European Scientific Journal, ESJ, 2018)
This study evaluated the principals’ instructional supervision practices as key to Kiswahili academic performance in public day secondary schools in Nairobi County, Kenya. Secondary school principals’ instructional practices are paramount in enhancing academic performance among secondary school students. Quality and relevant instruction ensures excellent academic Kiswahili achievement of students. Through instructional supervision offered by the principals, teachers are stimulated, supported and motivated to instruct the students well. For instructional supervision to fully benefit schools, both the principals and the teachers need to play a meaningful and effective role. The improvement of school through instructional supervision has been a concern for education stakeholders in Kenya during colonial and after colonial periods. As a result, Education Commissions which were formed to evaluate the education system in Kenya addressed the status of Kiswahili. The education Commissions included Phelps Commission of 1924 which recommended the use of vernacular and Kiswahili for teaching practical subjects, and Presidential Working Party for the Establishment of Second University of 1981 which called for teaching of Kiswahili as a compulsory and examinable subject in both primary and secondary schools. The current study targeted 26 public day secondary schools, 26 principals, 26 heads of department of Kiswahili and 2664 students. Both probability and nonprobability sampling techniques were used in the study. The objectives of the study included: What instructional materials are used by Kiswahili teachers to ascertain performance in Kiswahili; what measures are put in place by secondary school principal to realize performance in Kiswahili; what are the strategies directed towards enhancing Kiswahili teachers’ skills in public day secondary schools in Nairobi County. Descriptive research design was adopted for the study. Data analysis techniques included stratified random sampling, proportional allocation, simple random sampling design and purposive sampling designs. Instruments for data collection included two sets of questionnaires and interview guide. Statistical Package for Social Sciences (SPSS) was used to calculate frequencies and percentages. The key findings of the study were that lack of the instructional materials may have contributed to poor performance in Kiswahili; school principals executed their duties properly as concerns Kiswahili teachers’ lesson attendance and that lack of concern of principals in what students learn in school may have led to poor performance in Kiswahili.